Cerebral analgesic response to nonsteroidal anti-inflammatory drug ibuprofen. Issue 7 (July 2015) - Hodkinson, Duncan J.; Khawaja, Nadine; O'Daly, Owen; Thacker, Michael A.; Zelaya, Fernando O.; Wooldridge, Caroline L.; Renton, Tara F.; Williams, Steven C.R.; Howard, Matthew A.
Abstract : Abstract: Nonopioid agents, such as nonsteroidal anti-inflammatory drugs (NSAIDs), are the most commonly used class of analgesics. Increasing evidence suggests that cyclooxygenase (COX) inhibition at both peripheral and central sites can contribute to the antihyperalgesic effects of NSAIDs, with the predominant clinical effect being mediated centrally. In this study, we examined the cerebral response to ibuprofen in presurgical and postsurgical states and looked at the analgesic interaction between surgical state and treatment. We used an established clinical pain model involving third molar extraction, and quantitative arterial spin labelling (ASL) imaging to measure changes in tonic/ongoing neural activity. Concurrent to the ASL scans, we presented visual analogue scales inside the scanner to evaluate the subjective experience of pain. This novel methodology was incorporated into a randomized double-blind placebo-controlled design, with an open method of drug administration. We found that independent of its antinociceptive action, ibuprofen has no effect on regional cerebral blood flow under pain-free conditions (presurgery). However, in the postsurgical state, we observed increased activation of top–down modulatory circuits, which was accompanied by decreases in the areas engaged because of ongoing pain. Our findings demonstrate that ibuprofen has a measurable analgesic response in the human brain, with the subjective effects of pain relief reflected in two distinct brain networks. The observed activation of descending modulatory circuits warrants further investigation, as this may provide new insights into the inhibitory mechanisms of analgesia that might be exploited to improve safety and efficacy in pain management. Abstract : Supplemental Digital Content is Available in the Text.Arterial spin labelling imaging demonstrates that ibuprofen has a measurable analgesic response in the human brain, with the subjective effects of pain relief reflected in 2 distinct brain networks.